Sektor Pariwisata Nasional: Komponen dan Keterkaitannya - Ivantia Savitri Mokoginta (Bina Ekonomi, 1999)
Tourism sector can play an important role in Indonesian economy, in term of generating foreign exchange as well as creating employment. The chain of product distribution in Tourism is different from that in other economic sectors. In addition, the number of 'actor' involved in Tourism is also bigger than that in other sectors. Therefore, multiplier effect from tourism sector is greater than the effect of multiplier in other economic sectors. This paper will try to give an adequate information of product distribution chain in tourism and its components.